Procesy produkcyjne i warunki pracy podstawą wzrostu konkurencyjności przedsiębiorstw przemysłu spożywczego - Cierniak-Emerych, Anna (The Manufacturing Processes and Working Conditions as the Basis of Growth of Competitiveness of Enterprises of Food Industry, 2006)
In the following description the problems of growth of competitiveness of enterprises are considered in connection with shaping working conditions paying particular attention to their development in the sphere of production. At the same time chosen community directives concerning working conditions and their influence on improvement in productive processes in enterprises functioning in Poland are emphasised.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 135-140